HUBUNGAN ANTARA PENGHARGAAN DIRI DAN KEMAMPUAN MENULIS OLEH SISWA TAHUN PERTAMA DI SMAN 1 PEKANBARU - Rizka Desia Asri; Jismulatif Jismulatif (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
The objective of this research is to determine the correlation between self-esteem and writing ability of the first year students of SMAN 1 Pekanbaru. This is a correlational research that hastwo variables. The sample of this research is one class consisted of 36 students. The class was chosen by using Cluster Random Sampling Technique. Self-esteem questionnaire and writing test were used to collect the data. The self-esteem data were collected by using a set of questionnaire FLSES (Foreign Language Self-Esteem Scale) designed by Hassan (2001). The data of writing ability were taken by administaring test of writing. The collected data were analyzed by using Pearson Product Moment Correlation. The result shows that there is low correlation between students’ self-esteem and writing ability with the correlation value 0.312, while the coefficient correlation is as big as 9.7 %. The self-esteem of the students is categorized in “average” level and the writing ability is categorized in “good” level. It indicates that the students’ self-esteem influences their writing ability. Based on the finding, probably it would be better for the students to pay attantion on personality aspect, such as self-esteem in learning process of writing.